Development of waste coir-reinforced aluminum matrix automotive brake pad material - Afdzaluddin, Atiqah; Maleque, Md. Abdul; Zamani, A. R. (2012)

(untitled)
High friction and low wear are the prime functional properties of a brake pad material. Therefore main ingredients of brake pad materials are filler or reinforcement material, binder, friction modifiers, abrasive material and solid lubricant. There is a growing tendency to replace the asbestos filler in brake friction materials. Therefore, this paper presents a new development of waste-reinforced aluminum matrix automotive brake pad materials with a view to replace the use of asbestos whose dust is carcinogenic and has a harmful effect to the human life. In this research, five different laboratory formulations were selected with varying waste coir fiber as reinforcement consists of 0, 5, 10, 15, and 20 volume fraction along with binder, friction modifiers, abrasive material and solid lubricant using powder metallurgy technique. The coir fibre reinforced composite sample with a size of 25 mm x 25 mm x 6 mm was fabricated for physio-mechanical and tribological testing. The density and microstructural analysis were performed using densometer and SEM respectively whereas, hardness and compressive tests were done using hardness and universal testing machine respectively. The CHASE Dynamometer machine in accordance with Society of Automotive Engineer standard procedure SAE J661 was employed for tribological properties of the developed brake pad materials. From the study it was observed that two formulations with 5 and 10% volume fraction waste coir fibre were able to show better properties in terms of physico-mechanical, wear and friction compared to other formulations. The microstructure reveals uniform distribution of constituent’s materials along with the coir fiber in the morphology. It can be concluded that the new coir fibre (up to 10%) might be suitable for better physico-mechanical and tribological properties. Hence, waste coir fiber can be used as a candidate fibre or filler material for the mass-scale fabrication of asbestos-free brake pad without any harmful effect.